2016
DOI: 10.5937/sjm11-9241
|View full text |Cite
|
Sign up to set email alerts
|

Environmental concern to attitude towards green products: Evidences from India

Abstract: Environmental concern is defined as the degree of consumers' awareness of environmental problems and their willingness to contribute personally to the solution of these problems (Dunlap & Jones, 2002; Kim & Choi, 2005). It can also be defined as the degree of consumer worry about the threats to environment due to human interventions (Hassan, 2014). The recent environmental crises have increased the environmental concern of consumers around the world. In fact, the magnitude of the existing environmental problem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 31 publications
3
30
0
4
Order By: Relevance
“…Similarly, Schultz and Oskamp [45] noted that environmental concern influences attitude towards environmental issues and thus determines the effort people were willing to exert in order to recycle. In addition, environmental concern had a significant influence on the implementation of recycling [46] and attitude towards green products [47]. Laroche, Bergeron, and Barbaro-Forleo [48] stressed that consumers with environmental awareness were willing to pay more for environmentally friendly products.…”
Section: Environmental Concernmentioning
confidence: 99%
“…Similarly, Schultz and Oskamp [45] noted that environmental concern influences attitude towards environmental issues and thus determines the effort people were willing to exert in order to recycle. In addition, environmental concern had a significant influence on the implementation of recycling [46] and attitude towards green products [47]. Laroche, Bergeron, and Barbaro-Forleo [48] stressed that consumers with environmental awareness were willing to pay more for environmentally friendly products.…”
Section: Environmental Concernmentioning
confidence: 99%
“…The study results support both multi mediating relationships. Kirmani and Khan (2016) suggests that more studies are needed on green marketing from developing countries, including China, India, etc. Similarly, Agarwal and Kumar (2020) found that most studies in green marketing are from the United States based on three decades of literature.…”
Section: Discussionmentioning
confidence: 99%
“…The current study has focused on Pakistan's textile sector as it is one of the largest sectors that contributes significantly towards, exports, GDP, and employment generation (Memon et al, 2019). Additionally, the authors' feel that the textile sector of Pakistan needs to adopt green marketing for sustainable and competitive advantages Kirmani and Khan (2016), based on an extant literature review, suggested literature needs more studies on green advertising from Asian Countries, especially India and China, etc. that are facing problems related to environment degrading."…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The recent environmental crisis increased the environmental concerns of consumers. On the other hand, the impact of existing environmental problems and the environmental deterioration had been realized by the global consumers and consequently, they started to put effort for the protection of environment (Danish, & Naved, 2016). The environmental deterioration and sustainability are considered as the most crucial problems in our world and the awareness regarding all aspects of environment has improved (Dagher, & Itani 2014).…”
mentioning
confidence: 99%